Spectral analysis and design approach for high force to volume extrusion damper-based structural energy dissipation. - Rodgers, Geoffrey W.
High force to volume extrusion damping services can offer significant energy dissipation directly in structural connections and significantly reduce seismic response. Realistic force levels up to 400 kN have been obtained experimentally validating this overall concept. This paper develops spectral based design equations for their application. Response spectra analysis for multiple, probabilistically scaled earthquake suites are used to delineate the response reductions due to added extrusion damping. Representative statistics and damping reduction factors are utilized to characterize the modified response in a form suitable for current performance based design methods. Multiple equation regression analysis is used to characterize reduction factors in the constant acceleration, constant velocity, and constant displacement regions of the response spectra. With peak device forces of 10 percent of structural weight, peak damping reduction factors in the constant displacement region of the spectra are approximately 6.5 x 4.0 x and 2.8 x for the low, medium and high suites, respectivel. At T = 1 s, these values are approximately 3.6 x 1.8 x and 1.4 x, respectively. The maximum systematic bias introduced by using empirical equations to approximate damping reduction factors in design analyses is within the range of +10 to -20 percent. The seismic demand spectrum approach is shown to be conservative across a majority of the spectrum, except for large added damping between T = 0.8 an 3.5 s, where it slightly underestimates the demand up to a maximum of approximately 10 percent. Overall, the analysis shows that these devices have significant potential to reduce seismic response and damage at validated prototype device force levels.
Keywords: Lead dampers; Structural design; Response spectra; Seismic response; Design equations; Reduction factors